Theoretical Study on Characteristics of Glow Discharged Neon Gas and Its Interaction With Terahertz Waves - Hou, Lei; Wang, Yaodong; Wang, Junnan; Yang, Lei; Shi, Wei (Frontiers in Physics, 2021)
Discharge gases have been used to detect terahertz (THz) waves, however, there are few relevant theoretical studies. The neon glow discharge model is established by COMSOL Multiphysics software, the characteristics of glow discharged neon and the interaction of the discharged gas with THz waves were investigated. The results show that with the increase of THz wave’s frequency, the transmittance increases, The change of plasma discharge characteristics caused by THz wave can be used for THz wave detection. The results provide a theoretical basis for the development of cheap, room temperature THz wave detector with fast response speed, and high sensitivity.